Pengaruh Waktu Pengeringan Dan Tempering Terhadap Mutu Beras Pada Pengeringan Gabah Lapisan Tipis - Prasetyo, Totok; A, Kamaruddin; D, Made K; T, Armansyah H; N, Leopold (Universitas Muhammadiyah Yogyakarta, 2008)
The aim of this research was to determine the effect of various drying and tempering durations on rice quality using thin layer drying. The drying procedure consist four satge; first rough rice was dried in a drying chamber for various durations to remove 5 to 8 % moisture content (M.C). In the second stage rice was tempered under the room temperature for certain duration, to reduce MC gradients within the kernels. tempering period. The rice was then dried further to reach the final 14 % M.C. After the second drying the rice was tempered. Drying process was conducted using heated air at temperature of either 50 0C, RH 26% or 60 0C, RH 17%. The results show that very small reduction in Head Rice Yield (HRY) when less than 6 % m.c, were removed during the first drying stage. Effects on HRY was obeserved when the moisture removal was greater than 6% m.c. during the 1st drying stage. It was also observed that tempering time could not prevent the reduction in HRY when moisture remomal was higher than 6% M.C. during the 1st drying stage.